Phylogeny and morphology reveal a new species of Chlorociboria (Chlorociboriaceae, Leotiomycetes) from southwestern China - Li, Cui-Jin-Yi; Chethana, K.w. Thilini; Hyde, Kevin D.; Zhao, Qi (Phytotaxa, 2022)
A new species, Chlorociboria daliensis, was discovered on decayed decorticated wood in Yunnan Province, southwestern China. Chlorociboria daliensis can be distinguished from other Chlorociboria species by the colour of their discs which are light blue when fresh, pale yellowish-green, green or dark green when dry, branched paraphyses, cylindric or subclavate asci with J+, apical ring in Melzer’s reagent, elongate-ellipsoidal ascospores, and tomentum hyphae which are mostly absent. Phylogenetic analyses based on nLSU and ITS sequence data showed that C. daliensis forms a monophyletic group with a 99% maximum likelihood bootstrap support. The results of the pairwise homoplasy index (PHI) test revealed no significant genetic recombination (Φw = 1.0) between the closely related C. daliensis and C. poutoensis. The current study introduces the new species, C. daliensis, with a detailed description, illustrations, and a taxonomic key for Chlorociboria.